Expression of the herpes simplex virus 1 alpha transinducing factor (VP16) does not induce reactivation of latent virus or prevent the establishment of latency in mice. - Sears, A E (1991)
A feature of the cascade regulation of herpes simplex virus 1 gene expression in productive infection is that the first genes to be expressed, the alpha genes, are transactivated by a structural component of the virion designated as the alpha transinducing factor (alpha TIF). In this study, we have tested the hypothesis that latent infection of sensory neurons results from the failure of alpha TIF, a tegument protein, to be transported from the nerve endings to the nucleus of the sensory neuron. Two viruses were constructed. The first recombinant virus (R6003) contained a second copy of the alpha TIF gene placed under the control of a metallothionein promoter. The second recombinant virus (R6004) is identical to R6003 except for the presence of a stop codon inserted at amino acid 70 of the second alpha TIF gene. The metallothionein promoter inserted into the viral genome was shown to be expressed, and alpha TIF mRNA was detected by in situ hybridization of sections of trigeminal ganglia of mice infected with R6003, both untreated and those given cadmium injections. In all experiments, there were no significant differences in the recovery of latent virus from mice infected with R6003 or R6004, whether injected with cadmium or not. Cadmium administration at the time of infection and at intervals thereafter did not preclude establishment of latency. In another series of experiments, transgenic mice expressing the metallothionein-driven alpha TIF did not differ from nontransgenic siblings with respect to the incidence of latent virus in trigeminal ganglia. We conclude that the absence of alpha TIF cannot alone account for the establishment of latency.